Mexico : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report, 2016)
This paper discusses the findings and recommendations made in the Financial System Stability Assessment for Mexico. Mexico's economic fundamentals are strong. The medium-term outlook for the Mexican economy foresees steady growth underpinned by strong macroeconomic policies, broad reform initiatives, and relatively strong balance sheets. Key risks are external and include a U.S. growth slowdown, lower oil prices, and volatility in global financial markets. The financial system is broadly resilient, notwithstanding some weaknesses under certain adverse shocks. The solvency and liquidity stress tests of the banking system indicate that it can withstand severe adverse macro-financial shocks despite large capital losses in some cases.